Assessment of microbial activity by CO2 production during heating oil storage. Issue 8 (21st April 2022) - Surger, Maximilian J.; Blank, Lars M.
Abstract: Microbial activity is the driving force of the carbon cycle, including the digestion of biomass in the soil, oceans, and oil deposits. This natural diversity of microbial carbon sources poses challenges for humans. Contamination monitoring can be difficult in oil tanks and similar settings. To assess microbial activity in such industrial settings, off‐gas analysis can be employed by considering growth and non‐growth‐associated metabolic activity. In this work, we describe the monitoring of CO2 as a method for measuring microbial activity. We revealed that the CO2 signal corresponds to classical growth curves, exemplified by Pseudomonas fluorescens, Yarrowia lipolytica, and Penicillium chrysogenum . Deviations of the CO2 signal from the growth curves occurred when the yield of biomass on the substrate changed (i.e., the non‐growth‐associated metabolic activities). We monitored CO2 to track the onset of microbial contamination in an oil tank. This experimental setup was applied to determine the susceptibility of heating oil and biodiesel to microbial contamination long before the formation of problematic biofilms. In summary, the measurement of CO2 production by bacteria, yeasts, and molds allowed the permanent monitoring of microbial activity under oil storage conditions without invasive sampling.